2012
DOI: 10.1021/jp2119179
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Magnetic Superatoms and Assessment of van der Waals Dispersion Effects in Csn Clusters

Abstract: We report the global minimum (GM) structures and electronic properties of Cs n clusters with up to 80 atoms, obtained employing a density functional theory method which accounts for van der Waals dispersion interactions (vdW-DFT). The GM structures of Cs n are found to differ markedly from those of lighter alkali clusters like Na n . Three main physical factors are invoked to interpret the differences: vdW attraction, sd hybridization, and spin polarization. vdW effects are found to modify the GM structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Electronic structure calculations that Aguado performed [58] on the Cs 13 cluster, in fact, support this conjecture. He performed several calculations on the icosahedron (I h ), C 2 and C s isomers.…”
Section: Validity Of Hund's Rule In Clustersmentioning
confidence: 72%
See 4 more Smart Citations
“…Electronic structure calculations that Aguado performed [58] on the Cs 13 cluster, in fact, support this conjecture. He performed several calculations on the icosahedron (I h ), C 2 and C s isomers.…”
Section: Validity Of Hund's Rule In Clustersmentioning
confidence: 72%
“…This was in fact demonstrated for the first time in, what has by now become a cult paper in the area of cluster science, by Knight et al [3]. Na n clusters at sizes 8,18,20,40,58 and 92 were found to be more stable than the neighboring sizes. Analogy of the simple metal clusters was taken a step further when it was experimentally shown that clusters with one electron less than shell filling have large electron affinities (EA), like halogen atoms [4][5][6][7], and those with one electron more than shell filling have small ionization potentials (IP), like alkali atoms [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations